2009
DOI: 10.1080/13693780802227308
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiles ofTrichophyton rubrumin response to itraconazole

Abstract: Trichophyton rubrum is the predominant causative agent for superficial dermatomycosis. In order to understand how triazole antifungal agents interact with dermatophytes, the gene expression response of T. rubrum to itraconazole was studied by large-scale gene expression profiling. A total of 670 genes were found to be responsive to itraconazole, including 305 that were up-regulated and 365 down-regulated. Most genes involved in lipid metabolism and especially in ergosterol biosynthesis were up-regulated in res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…Similar and different groups were also observed in other fungi in response to different azoles [8,9,11,12,15] (Figure 5). Among the genes affected, we identified genes in common with other fungi, as well as genes unique to Paracoccidioides .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar and different groups were also observed in other fungi in response to different azoles [8,9,11,12,15] (Figure 5). Among the genes affected, we identified genes in common with other fungi, as well as genes unique to Paracoccidioides .…”
Section: Discussionsupporting
confidence: 84%
“…Because ERG transcripts and proteins levels were changed in the presence of azoles in fungi such as T. rubrum [9], S. cerevisiae [8], C. albicans [11,12] and A. fumigatus [13] we investigated whether ergosterol synthesis-related transcripts such as lanosterol 14 α-demethylase ( ERG11 ), C5,6-desaturase ( ERG3 ), delta-24-sterol C-methyltransferase ( ERG6 ), C-22 sterol desaturase ( ERG5 ) and C-4 methyl sterol oxidase ( ERG25 ) were changed in Paracoccidioides Pb 01 after 1 h, 2 h and 6 h of exposure to itraconazole using specific oligonucleotides in qRT-PCR. The results showed that all transcripts were increased at all time points (Figure 2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify additional factors that play a role during infection, investigators have examined the transcriptional response of dermatophytes exposed to environmental factors such as growth on lipids [37, 38], changes in pH [38, 39], and the presence of antifungal drugs [38, 4045]. They have also assessed transcript abundance during different stages of growth [4649].…”
Section: Virulence Factor Identificationmentioning
confidence: 99%
“…Using a similar methodology, it was found that efinaconazole did not increase the MIC in one Trichophyton mentagrophytes strain (data not shown). Antifungal drug exposure is believed to induce a stress response in fungal cells, leading to decreased drug susceptibility via a variety of mechanisms, such as the induction of drug efflux pumps (13). To assess the effects of efinaconazole exposure on the susceptibility of T. rubrum to commercially available antifungal drugs, the MICs of itraconazole, terbinafine, amorolfine, and ciclopirox were also determined.…”
mentioning
confidence: 99%